Jazz country : Ralph Ellison in America - Porter, Horace A., 1950- (Book collections on Project MUSE., 2001)
The first book to reassess Ralph Ellison after his death and the posthumous publication of Juneteenth, his second novel, Jazz Country: Ralph Ellison in America explores Ellison's writings and views on American culture through the lens of jazz music.